Flowering Plants : Nightshades to Mistletoe - Mohlenbrock, Robert H. (Book collections on Project MUSE., 1990)
This sixth volume of dicots contains three orders and eight families. The orders included are Solanales, Campanulales, and Santalales. Within the Solanales are the families Solanaceae, Convolvulaceae, Cuscutaceae, and Polemoniaceae. The Campanulales contain only the family Campanulaceae. The Santalales include the families Celastraceae, Santalaceae, and Viscaceae. As with each volume in this series Mohlenbrock includes a complete plant description, illustrations showing diagnostic features, distribution maps, and ecological notes.